Multimodal retrieval in the medical domain : First International Workshop, MRMD 2015, Vienna, Austria, March 29, 2015 : revised selected papers /: First International Workshop, MRMD 2015, Vienna, Austria, March 29, 2015 : revised selected papers. ([2015]) - Unknown
No abstract available